2018
DOI: 10.1186/s13046-018-0691-9
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Integrin-β5, a miR-185-targeted gene, promotes hepatocellular carcinoma tumorigenesis by regulating β-catenin stability

Abstract: BackgroundThe tumour microenvironment is essential for cancer progress and metastasis. Integrin-β5 (ITGB5), a member of the integrin family, has been implicated to mediate the interactions of cells with the extracellular matrix (ECM) and promote tumorigenesis in several malignancies. However, the role of ITGB5 in hepatocellular carcinoma (HCC) is still unknown.MethodsThe biological function of ITGB5 in HCC was investigated using migration, colony formation assays. The potential molecular mechanism of ITGB5 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 38 publications
2
38
0
Order By: Relevance
“…In this study, the mechanism of DC-SIGN upregulation in CRC was mainly elucidated in the following two aspects. First, we found miR-185 targets DC-SIGN mRNA by binding to the DC-SIGN 3′-UTR to downregulate DC-SIGN expression, which confirmed previous findings that miR-185 regulates gene expression by initiating mRNA degradation and functions as a tumor suppressor [26,27]. We also found that the low miR-185 expression level was associated with CRC metastasis.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, the mechanism of DC-SIGN upregulation in CRC was mainly elucidated in the following two aspects. First, we found miR-185 targets DC-SIGN mRNA by binding to the DC-SIGN 3′-UTR to downregulate DC-SIGN expression, which confirmed previous findings that miR-185 regulates gene expression by initiating mRNA degradation and functions as a tumor suppressor [26,27]. We also found that the low miR-185 expression level was associated with CRC metastasis.…”
Section: Discussionsupporting
confidence: 89%
“…According to the datasets, we noticed that miR-185 is frequently downregulated in CRC and appears to be a promising biomarker [25]. miR-185 is involved in the suppression of the malignant process, especially tumor metastasis [26,27]. Several studies have documented that miRNAs frequently form feedback loops since they themselves are regulated by transcription factors that may, in turn, target directly or indirectly [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Integrins are heterodimeric cell surface receptors composed of α-subunits and 8 β-subunits, and modulate a variety of biological functions in tumorigenesis [20]. As previously described, ITGB1 is considered as a key adhesion receptor for ECM components and can contribute to cell proliferation, invasion and metastasis in various cancers [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…ITGB1 is crucial for fascin-mediated breast cancer stem cell function and disease progression [24]. Lin et al demonstrated that miR-185/ITGB5 played an essential role in the development of HCC through mediating β-catenin pathway [25]. In breast cancer cells, the tumorigenic ability could be facilitated due to the ITGB5mediated EMT induced by transforming growth factor β [26].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Hoshino et al proved that exosomal β5 integrin regulates liver tropism associated with liver metastasis in several tumors [ 12 , 13 , 24 ]. In a more recent study, Lin et al demonstrated that β5 integrin is highly expressed in HCC tissues, facilitating cancer cell growth and promoting cell migration [ 25 ]. In human HCC patients, fibrinogen [ 26 ] activates hepatic stellate cells (HSC) [ 27 ] and liver specific mesenchymal cells by binding αvβ5 integrin [ 28 ] widely expressed by neoplastic cells to promote liver disease progression and tumor metastasis [ 29 ].…”
Section: Introductionmentioning
confidence: 99%